Exploring the Microbiome Analysis and Visualization Landscape - Peeters, Jannes; Thas, Olivier; Shkedy, Ziv; Kodalci, Leyla; Musisi, Connie; Owokotomo, Olajumoke Evangelina; Dyczko, Aleksandra; Hamad, Ibrahim; Vangronsveld, Jaco; Kleinewietfeld, Markus; Thijs, Sofie; Aerts, Jan (Frontiers in Bioinformatics, 2021)
Research on the microbiome has boomed recently, which resulted in a wide range of tools, packages, and algorithms to analyze microbiome data. Here we investigate and map currently existing tools that can be used to perform visual analysis on the microbiome, and associate the including methods, visual representations and data features to the research objectives currently of interest in microbiome research. The analysis is based on a combination of a literature review and workshops including a group of domain experts. Both the reviewing process and workshops are based on domain characterization methods to facilitate communication and collaboration between researchers from different disciplines. We identify several research questions related to microbiomes, and describe how different analysis methods and visualizations help in tackling them.